Clinical features and prognostic factors of spinal fibroblastic/myofibroblastic tumors: a long-term, single-center, retrospective study - Sun,Haitao; He,Shaohui; Zhao,Yuechao; Ye,Chen; Yang,Xinghai; Xu,Wei; Xiao,Jianru (PeerJ, 2020)
Background Spinal fibroblastic and myofibroblastic tumors (FMTs) are extremely rare. Few studies have reported on the features and outcomes of this condition that affects the axial skeleton. We explored the clinical characteristics and factors affecting the prognosis of spinal FMTs. Methods We retroactively assessed the survival of 51 patients with spinal FMTs who underwent surgical and adjuvant treatments in our center between April 2006 and September 2018. Factors affecting disease-free survival (DFS) and overall survival (OS) were analyzed using the Kaplan–Meier method. Variables with p value ≤ 0.05 were subjected to multivariate analysis using the Cox proportional hazards regression model. A two-sided P value < 0.05 was considered statistically significant. Results The mean follow-up period was 50.8 ± 35.6 months (Range 4.2–172.6). Kaplan–Meier survival curves showed that the 5-year DFS was 10% (95% CI [31.09-42.56]) and the 5-year OS was 53% (95% CI [61.28–97.20]). Multivariate analysis showed that en bloc excision was associated with better DFS (HR 0.214, 0.011) and OS (HR 0.273, 0.043), radiotherapy negatively affected OS (HR 0.353, 0.033), and the recurrence and Ki-67 index <5% significantly affected DFS (HR 3.008, 0.008 and 2.754, 0.029). Conclusions Spinal FMTs are rare. Surgery is the treatment of choice and en bloc excision is strongly recommended to improve outcomes. Disease recurrence and the Ki-67 marker are correlated with the progression of these tumors.
Keywords: Fibroblastic/myofibroblastic tumor; Spine; En bloc excision; Clinical features; Prognosis; Radiotherapy; Survial analysis; Ki-67; Chemotherapy